High throughput fabrication of disposable nanofluidic lab-on-chip devices for single molecule studies - van Kan, Jeroen A. (American Institute of Physics, 2012)
An easy method is introduced allowing fast polydimethylsiloxane (PDMS) replication of nanofluidic lab-on-chip devices using accurately fabricated molds featuring cross-sections down to 60 nm. A high quality master is obtained through proton beam writing and UV lithography. This master can be used more than 200 times to replicate nanofluidic devices capable of handling single DNA molecules. This method allows to fabricate nanofluidic devices through simple PDMS casting. The extensions of YOYO-1 stained bacteriophage T4 and λ−DNA inside these nanochannels have been investigated using fluorescence microscopy and follow the scaling prediction of a large, locally coiled polymer chain confined in nanochannels.